Masculinidades : na perspectiva das famílias monoparentais no setor rural. (2022)
This article is carried out in order to present a reflection on Masculinities, from the perspective of single-parent families in the rural sector, making it known that families represent or are led from a male figure with a diversity of responsibilities, challenges, changes and Among other fundamental aspects, which are taken to the academic training and the upbringing of boys and girls. From there, the different stigmas and signaling to which the father figure is subjected must be analyzed, especially in rural areas, where he has been trained in a traditional society and the only thing that can be expected is the reciprocity of his training. Then the roles that for decades have been adapted both for women in a vision that represent the daily chores of a home and also those of men based on terms of authority, provision for the home will be analyzed. In this way, it is concluded that this reflection should lead to the rethinking of the upbringing of our children, where it is not defined by patriarchy or matriarchy, but rather an act of conscience for social development, emotional, physical, and cultural of our children of the future.